High levels of kappa free light chain synthesis predict cognitive decline in relapsing-remitting multiple sclerosis - Rosenstein, Igal; Axelsson, Markus; Novakova, Lenka; Rasch, Sofia; Blennow, Kaj; Zetterberg, Henrik; Lycke, Jan (Frontiers in Immunology, 2023)
Background Evolving evidence suggests that measurement of cerebrospinal fluid (CSF) kappa free light chain (KFLC) synthesis has high diagnostic sensitivity and specificity for multiple sclerosis (MS), but its prognostic ability is less investigated. The usefulness of KFLC in predicting cognitive impairment (CI) is still unknown. Methods In a monocentric longitudinal retrospecitve cohort study, KFLC-index ([CSF KFLC / serum KFLC] / [CSF albumin / serum albumin]) measured by latex-enhanced immunonephelometry was prospectively determined as part of the diagnostic workup in patients with early relapsing-remitting MS (RRMS, n=77). The ability of KFLC-index to predict information processing speed (IPS) worsening as assessed with the symbol digit modalities test (SDMT) was investigated in univariable and multivariable models. Results In patients with KFLC-index>100 (n=31), 11 subjects (35.5%) showed reduced SDMT scores by ≥8 points at follow-up (mean follow-up time 7.3±2.6 years), compared with their baseline scores (p=0.01). Baseline KFLC-index>100 was strongly associated with a higher hazard of SDMT score reduction at follow-up (adjusted hazard ratio 10.5, 95% confidence interval 2.2-50.8, p=0.003; median time to SDMT reduction 7 years). Conclusion Intrathecal KFLC synthesis has become an attractive diagnostic tool for MS. We show for the first time that in a real-world setting of early RRMS, KFLC-index predicted cognitive decline. Whether this predictive ability of KFLC-index also concerns other cognitive domains than IPS, warrants further investigations. Key words: Multiple sclerosis, biomarkers, kappa free light chains, cognitive impairment, symbol digit modalities test.